Pola Pengasuhan Orang Tua Dan Moral Remaja Dalam Islam - Miftahul Jannah (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2015)
Style of parenting can`t be separated by moral behavior in educating children, how to have morals in life, especially in the family environment and parents this sekolah.Dewasa many difficulties and problems in educating children, from academics, intellectuals, state officials moreover from lower socioeconomic circles who have no education and mature economies. The problem lies in the failure of parents to educate generations obedient to Allah and will understand Islamic values. Various problems occur for example brawl, free sex, lack incapacity to control children in the associate, drugs, and various other criminal. Events and these events often occur in big cities but now shifts to all levels of society, both in rural and metropolitan cities. The teenagers went along with all the negative behavior without thinking about the impact of the negative impacts that will be experienced both for himself and his parents have failed to maintain the good name of both parents in the world and in the presence of Allah, for failing to do good deeds as an eternal charity before Allah Swt. Our country is far backward from the Islamic civilization since leaving the values of Islam, the developed world have left their ignorance and are following Islamic law that is believed to be true in the welfare of the ummah. Generani Islamic Ummah and Islam must educate by parents who have the foundation of Islam in the household so that kusesesan begins within the family nucleus and then continues into the school environment and the community. Abstrak: gaya pengasuhan orang tua tidak terlepas dengan moral dalam mendidik perilaku anak, bagaimana agar memiliki moral dalam kehidupan, terutama di lingkungan keluarga dan sekolah.Dewasa ini orang tua banyak mengalami kesulitan dan permasalahan dalam mendidik anak, b aik dari kalangan akademisi, intelektual, petinggi negara apalagi dari kalangan sosial ekonomi bawah yang tidak memiliki pendidikan dan ekonomi yang matang. Permasalahan orang tua terletak pada gagalnya mendidik generasi yang taat pada Allah Swt dan paham akan nilai-nilai keislaman. Berbagai masalah terjadi misalnya tawuran, free sex, ketidak sanggupan mengontrol anak dalam bergaul, narkoba, dan berbagai macam kriminal lainnya. Kejadian dan peristiwa ini sering terjadi di kota besar namun sekarang bergeser ke semua tingkatan masyarakat baik di desa, dan kota metropolitan. Para remaja ikut - ikutan dengan segala dampak perilaku negatif tanpa memikirkan dampak negatif yang akan dialami baik untuk dirinya dan orang tuanya telah gagal menjaga nama baik orang tua baik di dunia dan di hadapan Allah Swt, karena gagal dalam beramal shalih sebagai amal yang kekal di hadapan Allah Swt. Negara kita jauh mundur ke belakang dari peradaban Islam karena meninggalkan nilai-nilai islam, dunia maju telah meninggalkan kejahilan mereka dan sedang mengikuti syariat islam yang diyakini kebenarannya dalam mensejahterakan ummat. Ummat islam dan generani Islam harus didik oleh orang tua yang memiliki landasan keislaman dalam rumah tangga sehingga kusesesan di mulai dalam keluarga inti kemudian berlanjut ke dalam lingkungan sekolah dan masyarakat Kata kunci: Pola Pengasuhan orang tua, moral dan remaja